PROBABLE FORECASTING IN THE COURSE OF INTERPRETING - Ye. B. Kagan; Yu. Yu. Shadrina (Russian State Vocational Pedagogical University, 2017)
Introduction. Translation practice has a heuristic nature and involves cognitive structures of consciousness of any interpreter. When preparing translators, special attention is paid to the development of their skill of probable forecasting.The aim of the present publication is to understand the process of anticipation from the position of the cognitive model of translation, development of exercises aimed at the development of prognostic abilities of students and interpreters when working with newspaper articles, containing metaphorical headlines.Methodology and research methods. The study is based on the competence approach to the training of students-translators, the complex of interrelated scientific methods, the main of which is the psycholinguistic experiment. With the use of quantitative data the features of the perception of newspaper texts on their metaphorical titles are characterized.Results and scientific novelty. On the basis of the conducted experiment to predict the content of newspaper articles with metaphorical headlines it is concluded that the main condition of predictability is the expectation. Probable forecasting as a professional competence of a future translator is formed in the process of training activities by integrating efforts of various departments of any language university. Specific exercises for the development of anticipation of students while studying the course of translation and interpretation are offered.Practical significance. The results of the study can be used by foreign language teachers of both language and non-language universities in teaching students of different specialties to translate foreign texts.